A preliminary study on the Average Maximum Velocity Sensitivity index from flow velocity variation in quality control for Color Doppler. (December 2021) - Fiori, Giorgia; Scorza, Andrea; Schmid, Maurizio; Galo, Jan; Conforto, Silvia; Sciuto, Salvatore Andrea
Abstract: Color Doppler (CD) is one of the most used ultrasound (US) Doppler techniques as it allows the 2D representation of blood flow. Even if a clarification on whether such technique provides qualitative or quantitative diagnostic information on velocity assessment is still awaited, the necessity of periodic Quality Control (QC) tests is ongoing. Consequently, in the present preliminary study, a previously proposed sensitivity parameter, namely the Average Maximum Velocity Sensitivity (AMVS), has been further investigated for Color Doppler QC. Three diagnostic US systems, equipped with phased array probes, have been used to collect Color Doppler images. Two Doppler phantom flow rate regimes and two US system settings have been employed during data acquisition. Despite the limitations encountered, the AMVS results are promising, therefore further studies should be carried out on CD clips, on a higher number of US systems and probes as well as on a greater number of phantom settings.